Dynamics of Older Teenagers’ Relation to Moral Values - Martišauskienė, Elvyda (Acta Paedagogica Vilnensia, 2001)
The article first of all represents comparison of attitudes toward moral values of earlier (who studied in year 1984-1985) and contemporary secondary school students. Understanding the importance of particular moral value was chosen as a criterion of an attitude. Within it 4 levels of attitude were defined. The research data revealed that attitudes of contemporary teenagers toward justice and sensitiveness is much more positive. At the same time their attitudes toward dutifulness and responsibility have become less positive then of earlier students. Comparison of behaviour traits of both groups of the teenagers also revealed some common traits and some differences. Comparison of both teenagers themselves and their peers’ responses gave a basis to think that contemporary teenagers are mare just, responsible and a little bit more sensitive. On the other side opinions of boys and girls about behaviour of their mates differ: girls are tended to evaluate it mare positively, boys - less positively.
Keywords: Moral education; older teenagers; moral values; sensitivity; responsibility; justice.